2011
DOI: 10.1017/s1751731111000887
|View full text |Cite
|
Sign up to set email alerts
|

Responses of feeding prebiotics on nutrient digestibility, faecal microbiota composition and short-chain fatty acid concentrations in dogs: a meta-analysis

Abstract: The effects of prebiotics on digestibility, short-chain fatty acid (SCFA) concentrations and bacterial populations in the faeces and immunity in dogs were evaluated by meta-analyses. Overall, data from 15 published studies containing 65 different treatment means of 418 observations from different breeds of dogs were included in the data set. Feeding of prebiotics to dogs did not affect the nutrient intake (P . 0.10), nor did prebiotics change (P . 0.10) the digestibility of dry matter (DM) and fat. However, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
(41 reference statements)
2
25
0
Order By: Relevance
“…144 Meta-analysis of 15 studies including 65 different treatment conditions showed that fecal SCFAs concentrations increase linearly with prebiotic dose. 145 This analysis also revealed that fecal Bifidobacteria and Lactobacillus increase with prebiotic dose, although no changes were observed for pathogenic C. perfingens or E. coli. The impacts of prebiotics were not related to the composition of the dog's diet, suggesting that prebiotic therapies can provide benefits independent of diet.…”
Section: Prebioticsmentioning
confidence: 83%
See 1 more Smart Citation
“…144 Meta-analysis of 15 studies including 65 different treatment conditions showed that fecal SCFAs concentrations increase linearly with prebiotic dose. 145 This analysis also revealed that fecal Bifidobacteria and Lactobacillus increase with prebiotic dose, although no changes were observed for pathogenic C. perfingens or E. coli. The impacts of prebiotics were not related to the composition of the dog's diet, suggesting that prebiotic therapies can provide benefits independent of diet.…”
Section: Prebioticsmentioning
confidence: 83%
“…In 1 study, chicory root, a source of inulin, improved fecal scores, increased Bifidobacteria , and decreased C. perfringens in the feces of healthy dogs . Meta‐analysis of 15 studies including 65 different treatment conditions showed that fecal SCFAs concentrations increase linearly with prebiotic dose . This analysis also revealed that fecal Bifidobacteria and Lactobacillus increase with prebiotic dose, although no changes were observed for pathogenic C. perfingens or E. coli .…”
Section: Therapeutic Manipulation Of the Gastrointestinal Microbiomementioning
confidence: 96%
“…First, prebiotics can be offered as a fixed percentage of dry matter. Indeed, most well-controlled prebiotic papers in cats and dogs report the dose of prebiotics in percentage of dry matter intake, varying from 0% to 7% (Patra, 2011). A potential issue with this way of administering prebiotics (i.e., as percentage of dry matter) is that the amount of food consumed by a given pet cat or dog may vary substantially over time (e.g., accordingly to age) and among different animals (e.g., two dogs, each weighting 10 kg, may consume different amounts of food).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown an effect of these ingredients on fecal microbial composition, nutrient digestibility, and short-chain fatty acid concentrations, particularly in dogs (Patra, 2011; Schmitz & Suchodolski, 2016; De Godoy, Kerr & Fahey, 2013). Domestic cats are obligate carnivores but several studies support the hypothesis that microbial fermentation inside the distal gut is significant and beneficial to the host (Rochus, Janssens & Hesta, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Barry et al [4] demonstrated that faecal concentrations of Clostridium perfringens, Lactobacillus and Bifidobacterium were not affected in healthy dogs when 0.2% or 0.4% inulin or scFOS was added to the diet. The results of prebiotic supplementation on intestinal microflora may be better during a disease challenge when the numbers of beneficial bacteria in the colon are decreased [37] . Heinrichs et al [33] reported that the reason for the lack effect of prebiotic supplementation on faecal bacterial populations might be that calves used in their study were healthy.…”
Section: Concentrations Of Faecal Scfamentioning
confidence: 99%